Is percutaneous Achilles tendon lengthening safe and effective for older children with idiopathic toe walking? - Stephanie T. Kha, MD; Halle D. Freiman, MD; Danika Baskar, MD; James G. Gamble, MD, PhD; Steven L. Frick, MD (Journal of the Pediatric Orthopaedic Society of North America, 2024)
ABSTRACT: Background: Treatment of older patients with idiopathic toe walking (ITW) can be challenging. Percutaneous Achilles tendon lengthening (pTAL) restores a normal gait pattern for younger children with ITW, but outcomes for older children are unclear. Concern exists that Achilles tendon lengthening in older children may cause residual calf weakness. Methods: We retrospectively evaluated 19 ITW patients older than 10 years of age who were treated with pTAL from 2001 to 2022, 17 of whom had documented ankle equinus with the knee in both extension and flexion in the clinic and in the operating room under anesthesia. Primary outcomes were absence of surgical complications, restoration of ankle motion and normal heel-toe gait pattern, and the ability to voluntarily toe walk and heel walk. Secondary outcomes were residual symptoms, limitations in mobility, use of regular shoewear, and self-reported parent satisfaction with the surgical procedure. Results: Mean age at time of surgery was 12.6 years (range 10–17 years), and average follow-up was 30.3 months (range 11.3–129 months). Seventeen patients (89%) had an Achilles tendon contracture pre-operatively, while two patients had passive ankle motion to neutral position with the knee in flexion. At final follow-up, fourteen patients reported no involuntary toe-walking; five patients reported occasional involuntary toe walking. All patients could voluntarily walk on toes and heels, had active ankle dorsiflexion at or above neutral, and had returned to full unrestricted activity. Most patients wore regular shoes. All parents reported satisfaction with the surgical procedure. Conclusions: The majority of older ITW patients have an Achilles tendon contracture and pTAL is a safe and effective treatment for these older patients. The procedure restores a normal heel-toe gait with no subjective residual ankle plantarflexion weakness. Key Concepts: (1) Achilles tendon contracture can develop in Idiopathic toe walker (ITW) patients as they age and walk on their toes. (2) Percutaneous achilles tendon lengthening (pTAL) is safe and effective in older ITW patients with or without Achilles contracture. (3) The pTAL procedure in older ITW patients can help restore a normal heel-toe gait with no residual ankle plantarflexion weakness. Level of Evidence: IV